(3hbGjI GdgOGjI YfhGf GdebOeIs - (3GdCYQLj, GdMSjfj, GdgGTej, GdfLaj, oRnhjf, CMeO Hf MHjH Hf CMeO, J (B1267(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg QH GdYGdejf(B...(3hHYO agPg LedI hGajI aj GdcdGe hfNHI TGajI aj GdeQGe (B...(3gd jLhR GdHbGA Ydi JbdjO GdeLJgO HYO ehJg Ce dG(B...s
(3BNQgG (B:s
(3dG jHbi CeQ hdG Jcdja hdG Mce MJi jJHY aJOHQ hGZJfe hCeYf GdfXQ MJi dG jahJc TjA ef gPg GdeWGdH GdLdjdI hGdMeO ddg ChdG hBNQG(B...s
(3fSNI HNW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B1(3,U(B109s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B117s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs